2017
DOI: 10.4049/jimmunol.1600193
|View full text |Cite
|
Sign up to set email alerts
|

Human Blood CD1c+ Dendritic Cells Encompass CD5high and CD5low Subsets That Differ Significantly in Phenotype, Gene Expression, and Functions

Abstract: There are three major dendritic cell (DC) subsets in both humans and mice, that is, plasmacytoid DCs and two types of conventional DCs (cDCs), cDC1s and cDC2s. cDC2s are important for polarizing CD4 naive T cells into different subsets, including Th1, Th2, Th17, Th22, and regulatory T cells. In mice, cDC2s can be further divided into phenotypically and functionally distinct subgroups. However, subsets of human cDC2s have not been reported. In the present study, we showed that human blood CD1c cDCs (cDC2s) can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 62 publications
11
123
1
Order By: Relevance
“…Recently, it has been reported that human cDC2 in tonsils, lymph nodes (LN), and blood as well as skin Langerhans and dermal DCs and blood pDCs can be further subdivided into CD5 positive and negative subpopulations, demonstrating for the first time that some human DCs express CD5 . In this context, it has been observed that CD5 is also expressed in DCs in mice (Burgueño‐Bucio et al., unpublished data).…”
Section: Cd5 General Remarksmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, it has been reported that human cDC2 in tonsils, lymph nodes (LN), and blood as well as skin Langerhans and dermal DCs and blood pDCs can be further subdivided into CD5 positive and negative subpopulations, demonstrating for the first time that some human DCs express CD5 . In this context, it has been observed that CD5 is also expressed in DCs in mice (Burgueño‐Bucio et al., unpublished data).…”
Section: Cd5 General Remarksmentioning
confidence: 96%
“…Recently, it has been reported that human cDC2 in tonsils, LN, and blood can be subdivided based on their CD5 expression. Interestingly, those DCs with high CD5 expression showed increased migration toward CCL21, due to an augmented CCR7 expression, and induced higher T cell proliferation and IL‐10, IL‐17, IL‐22, and IL‐4 production . Another study has demonstrated that skin Langerhans and dermal DCs can also be subdivided based on CD5 expression: CD5+ skin DCs are more potent at inducing CD8+ and CD4+ T cell proliferation and increased production of granzyme B, IFN‐γ, and TNF‐α in CD8+ T cells and IL‐22 in CD4+ T cells .…”
Section: Role Of Cd5 In Dendritic Cell Biologymentioning
confidence: 99%
“…Expression profiling has now provided a suite of more consistent markers that perform well across species, such as CLEC9A, CADM1, BTLA and CD26 for CD141 + myeloid cDC1, and CD2, Fc ε R1 and SIRPA for CD1c + myeloid cDC2 (Table ). Additional complexity discussed below is the emergence of subsets of cDC2 and the realization that conventional pDC gates include myeloid cDC precursors that also express CD123 and CD303 …”
Section: The Unified Classification Of Mammalian DCmentioning
confidence: 99%
“…Detailed phenotyping and single‐cell gene expression studies have recently characterized two subsets of cDC2 in human blood, one ‘DC‐like’ with higher expression of CD5, CD1c, HLA‐DQ and IRF4 and the other more ‘monocyte‐like’ showing CD14, CD32, CD36, CD163 and proportionately higher MAFB expression . CD14 + CD1c + cells have previously been detected and characterized as CD1c + monocytes but by gene expression, most cluster with cDC2 .…”
Section: Irf4/klf4/notch2‐dependent Myeloid Cdc2mentioning
confidence: 99%
See 1 more Smart Citation